China's enterprise reform : changing state/society relations after Mao - You, Ji, 1955- (London ; New York : Routledge, 1998)
The author demonstrates how China's post-Mao reforms have produced a quiet revolution from below as the process of political and economic liberalization has accelerated.
pt. I. Reshaping state and society relations. 1. Introduction. 2. A quiet revolution from below pt. II. Depoliticisation: diminishing party controls. 3. The reform of the enterprise leadership structure. 4. The party's organisational reform. 5. Withering of the party's industrial apparatus pt. III. De statisation: an analysis of the wage structure. 6. The dynamics of the industrial wage reform. 7. The politics of the industrial wage reform pt. IV. De statisation: an ownership and organisational analysis. 8. Corporatisation and privatisation. 9. The construction of a new economic model. 10. Concluding remarks.
Includes bibliographical references (pages 247-262) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: China -- Economic conditions -- 1976-2000.; China -- Economic policy -- 1976-2000.; China -- Politics and government -- 1976-; Chine -- Conditions économiques -- 1976-2000.; Chine -- Politique économique -- 1976-2000.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic history; Economic policy; Politics and government; China; Since 1976